THE STATUS OF SOIL PHOSPHORUS AT DIFFERENT CROPPING SYSTEM IN PANGALENGAN, SOUTH BANDUNG - Sri Djuniwati; Heru Bagus Pulunggono (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
The fixation of P in soils is dynamic in nature and the behavior of P-fraction may change with time and cropping system. Application of organic matter to soil under upland soil have been reported to decrease P-sorption and increase P-desorpion. Pangalengan, South Bandung in west Java is one of the wet humid area of Indonesia that has high rain fall, covered mainly by tropical humid forest, volcanic area with fertile volcanic soil. The objective of this study were to describe and compare some chemical characteristic and behavior of P-fraction as a function of crops and slope of the land in the farming system in Pangalengan, South Bandung, West Java, Indonesia. Soil samples from the surface soil (0-20 cm) were collected from 15 locations based on different planted crops (Tea, Vegetables, Forest, and Intercropping crops), and level of slope of the land areas of Cihawuk village, District Kertasari, Kecamatan Pangalengan. The result of the study showed that C-organic content of soil samples from 15 location of planted crops was slightly high (3.04-4.92 %) but total Nitrogen was low (0.22-0.45 %), wih soil reaction (pH H2O) was slightly acids (5.60-6.30) and pH (KCl) was lower than pH(H2O) (4.60-5.70). The available-P was low (3.50 – 7.10 ppm), but the HCl 25 % P from tea and vegetables location was higher than from forest and intercropping crops. Majority of P fraction from tea and vegetable location was Al-P fraction, but from Forest and intercropping crops was Ca-P fraction. The order of P fraction were Al-P > Ca-P> reductant soluble-P>Fe-P in tea and vegetables locations, but in the forest and intercropping were Ca-P> reductant-P > Al-P > Fe-P. However, The data showed that the total P (P-organic + P-inorganic) from tea and vegetables crop location was higher, and was dominated by inorganic form, than from forest and intercropping location was dominated by organic form. However, the slope did not affect the pattern of P-fractions and the sources of organic matter added or accumulated in those location formerly affected the amount and the pattern of P-fractions.